Mathematical Modeling of the Chagasic Trypanosomiasis (2019)
In this paper, we show an extended model that describes the dynamic interaction between the immune response of a mammal and Trypanosoma cruzi parasite during the acute phase of a Chagas Disease. The model considers the immune and cellular response, plus the different stages (intracellular and extracellular) of T. cruzi inside of a mammal host. The analysis of the time evolution of populations is made obtaining phase diagrams to determine the stability of the steady states in terms of its parameters. The system gives two steady states, which are associated with the Healing and Chronic state of the disease. The dead case obtained before when only the humoral immune response is considered it gets disappeared. The fundamental implication of this result is the benefit that the cellular immune response produces for the host as for the parasite since it allows to extend the life of the host while extending the critical state of the disease without destroying the habitat of the parasite.